On the sizing of a novel Flat-Panel ground heat exchanger in coupling with a dual-source heat pump. (November 2019) - Bottarelli, M.; Bortoloni, M.; Su, Y.
Abstract: Ground-coupled and air-source heat pumps (GCHPs and ASHPs, respectively) are regarded as energy efficient systems for air conditioning. Their coupling in a dual air and ground source heat pump (DSHP) can offer a further performance improvement by reducing the drawbacks of each standalone technology. In the present study, a DSHP coupled with a Flat-Panel as a horizontal ground heat exchanger (HGHE) is numerically analysed in comparison with its counterparts GCHP and ASHP, by implementing COMSOL Multiphysics to simulate heat transfer in the ground operated by the Flat-Panel. The DSHP operativity is provided by a function set to control the switching between air and ground sources, according to their temperatures and trigger thresholds. A parametric analysis has been then carried out in order to propose a preliminary guideline to size the Flat-Panel for a balance between energy saving and installation cost. The DSHP shows a higher efficiency in comparison with either ASHP or GCHP due to the switching between two sources to more favourable working temperatures, and can offer a profitable hybrid solution providing protection against frosting and size reduction of the HGHE, therefore helping to promote the penetration of heat pumps in the residential market. Highlights: A dual-source heat pump (DSHP) is numerically compared with its counterparts. The novel Flat-Panel (FP) is considered as horizontal ground heat exchanger. The switching between air and FP is controlled by an implemented function. A parametric analysis is carried out to propose guidelines for sizing the FP length. A DSHP coupled with FPs is an efficient and cost-effective air-conditioning system.